Significance of pH control in anammox process performance at low temperature. (October 2017) - Tomaszewski, Mariusz; Cema, Grzegorz; Ziembińska-Buczyńska, Aleksandra
Abstract: Anaerobic ammonium oxidation (anammox) is an efficient process for biological nitrogen removal from wastewater. Common use of this technology is still limited by relatively high optimal temperature. Temperature and pH influence on the anammox process was widely studied, but the significance of pH control in the anammox performance at low temperature was omitted. Moreover up to now, these two parameters were analyzed separately without looking into the composite effects. Statistical approach was used to conduct an in-depth study of the individual and interactive influence of pH and low temperature on the anammox activity. Optimal pH was observed between 7.0 and 7.5, but results indicate that there is no statistically significant interaction between pH and temperature. However, it was observed that the optimal pH range narrows along with the temperature decrease, which means that the efficiency of the anammox process at low temperatures can be improved by correction and adequate control of pH. Highlights: 15–20 °C constitutes breaking point for the anammox bacteria metabolism. No statistically significant interaction between pH and low temperature. Appropriate pH control can improves anammox efficiency at low temperatures.